(3OjhGf eMeO Hf haGs - (3eMeO haG GdTGPdj , eMeO Hf eMeO Hf eMeO GdScfOQj, TeS GdOjf CHhGdaJM,J (B760 (3g` s
(3ChdgG (B:s
(3eHJhQ, hjHOC GdehLhO efg Hbhdg(B: (3jHOj dg CTcGdkG ojTGgOgG s
(3BNQgG (B:s
(3eHJhQ CjVkG hjfJgj GdehLhO efg Hbhdg(B: (3hbO MTQ GdELeGY aj jhe LeYI Edi LGeY GdELeGY aj jhe LeYJj s
(3GdOjhGf TYQ Uhajs
(3GfXQ GdLRA GdChd HQbe (B271 (3COH HYfhGf OjhGf GHf haGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B487 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B206 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs